Electrodeposition of tin and tin chalcogenides from tin (II) methanesulfonate solution / Koay Hun Lee - Koay, Hun Lee (2014)
There were many researches had been done by scientists on electro-deposition of tin and tin chalcogenide thin films. Most of them were using SnCl2, Sn(EDTA), Sn(OH)2, SnSO4 and so on. But, there are not many studies have been done on the tin sulfoselenide (SnSSe) which is the derivative of the tin thin films. Therefore, an alternative for the tin ion source is tin (II) methanesulfonate to fabricate the tin and tin chalcogenide thin films. The process of electrodeposition of tin and tin chalcogenide thin films on the copper substrate by using a solution of tin (II) methanesulfonate (CH3SO3)2Sn (50 wt. % in H2O), natrium thiosulfate (Na2S2O3), natrium selenite (Na2SeO3) and methane sulfonic acid (CH3SO3H) is described. The chemical bath contained 0.01M tin (II) methanesulfonate, 0.01M natrium thiosulfate, 0.01M natrium selenite (Na2SeO3), and 40ml of methane sulfonic acid (99.5%) are prepared. Cyclic voltammetry (CV) experiments are conducted using potentiostat and galvanostat to study the reduction and oxidation potential. The CV experiments are conducted under different potential. The electrodeposition of Sn, SnS and SnSSe are observed and described. The characterization of the coated tin and tin chalcogenide thin films on the copper substrate were studied by using EDAX, SEM, AFM, XRF and XRD. The results of the characterization are studied. The electrodeposition of tin from tin (II) methanesulfonate solution with 1-butyl-1-methylpyrrolidinium trifluoro methanesulfonate (BMPOTF) ionic liquid at varying concentration was studied under the room temperature. Cyclic Voltammetry served to characterize the electrochemical behaviour of tin reduction and oxidation. The diffusion coefficient of stannous ions in the mixture of BMPOTF ionic liquid and MSA based electrolyte obtained via Randles-Sevcik was approximately 2.11 x 10-7cm2. Electroplating on copper panel was conducted under different current densities to determine BMPOTF based tin plating solution current efficiency. Mixture of BMPOTF and MSA based tin plating solution gave current efficiency as high as 99.9%. The deposit morphology of the mixture BMPOTF and MSA based tin coated substrates was observed by using EDX and SEM. A dense, fine and polygonal grain structure was obtained. Voltammetry and chronoamperometry for the electrodeposition of tin from tin (II) methanesulfonate mixed with ionic liquid and methane sulfonic acid at room temperature was studied. Cyclic voltammetry shows redox waves of tin (II), which proves that the electrodeposition of tin from tin (II) methanesulfonate is a diffusioncontrolled process. The diffusion coefficient of tin (II) ions in the solvent mixture showed good agreement from both voltammetry and chronoamperometry results. The diffusion coefficient of tin (II) in the mixture was much smaller than in aqueous solution, and it depends on the anion of the ionic liquid.